Development of Canva-based Educational Games on the Meaning of the Pancasila Principle Materials in Social Life for Grade IV Elementary Students - Marselina Tamba, Angel; Hadikusuma Ramadan, Zaka (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This paper examines the development of a Canva-based educational game on the meaning of the Pancasila principle learning material in social life for grade IV Elementary School students. This study uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model, but is limited to the development stage. The study was conducted at State Elementary School 167 Pekanbaru. Data collection techniques include interviews, product validation by linguists, material experts and media experts, as well as response tests from teachers and students. Data analysis was carried out qualitatively and quantitatively. The research results indicate that the Canva-based educational game is valid without revision. The validation results indicate 92% from linguists, 99% from the material expert, and 91% media experts, with a "Very Valid" criterion. While the percentage of values generated from teacher responses is 100% and student responses 97% with the "Very Practical" category. Based on the study results, the learning media developed is very feasible and practical to use as a learning medium for the meaning of the Pancasila principle learning material in social life for grade IV elementary students.